Country Partnership Framework for the Republic of Moldova for the Period FY18-21 - World Bank (World Bank, Washington, DC, 2017)
The quest for an alternative development model that underlies Moldova’s National Development Strategy (NDS), Moldova 2020, is a recognition that the two main drivers of economic growth and poverty reduction since the early 2000s are no longer sustainable. Growth was powered largely by consumption, and poverty reduction mainly by remittances and pensions. Since neither are expected to continue, future growth and poverty reduction will need to be driven increasingly by private sector-led job creation. Moreover, given the country’s vulnerability to changes in external demand and weather shocks, due to its small size, open economy, and reliance on agriculture, Moldova’s future development path will also need to include measures to renew and protect its human, physical, and social capital stock. Against this background, the main purpose of the FY18-21 Country Partnership Framework (CPF) is to support Moldova’s transition towards a new, more sustainable and inclusive development and growth model. It is grounded in the NDS, takes into account outcomes of the FY14-17 Country Partnership Strategy (CPS), and incorporates the three topmost priorities of the recent Systematic Country Diagnostic (SCD), namely: (a) strengthening the rule of law and accountability in economic institutions; (b) improving inclusive access to and the efficiency and quality of public services; and (c) enhancing the quality and relevance of education and training for job-relevant skills. These three priorities define and inform the CPF’s three focus areas: economic governance, service governance, and skills development, which are supplemented by climate change, a World Bank Group corporate priority, as a cross-cutting theme. The CPF incorporates key lessons learned during the last CPS, that political instability and governance challenges slow the pace of reform and that frequent personnel changes affect portfolio performance. Further, it assumes that the economic, political, and social stability experienced since January 2016 will continue at least until parliamentary elections in November 2018. Given that Moldova’s post-election political orientation, policy environment, and stability are uncertain, only the first half of the CPF (FY18-19) is programmed. Activities for the second half (FY20-21) will be defined during the FY19 Performance and Learning Review (PLR).